The Speech Function in Advertisements - Fitriany Fitriany (Journal of Language, Literature and Teaching, 2021)
The study aims to describe types of speech functions and reasons for using them in advertisements. Descriptive qualitative method is applied in this research with sentences found in the dialogue or conversation is the advertisement as the data of this research. The data collected is from the advertisement of electronic media. The research results in the finding of six types of speech function used in the advertisement which are the statement acknowledge statement, question, response statement to question, offer, and command with the statement as the dominant. These types are used in advertisements for descriptive and persuasive purposes.